Aquisição de imunidade passiva em cabritos alimentados com colostro de cabras com e sem mastite - Alcindo, J. F. [UNESP]; Braga, G. I. [UNESP]; Poló, T. S. [UNESP]; Deschk, M. [UNESP]; Narciso, L. G. [UNESP]; Peiró, J. R. [UNESP]; Marinho, M. [UNESP]; Mendes, L. C.N. [UNESP]; Feitosa, F. L.F. [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to evaluate the transfer of passive immunity goats kidded with mastitis to their kids. The animals were divided into two groups, namely: Group 1 (GI) containing kids, sons of goats without microbiological isolation in both mammary glands, and Group 2 (GII), composed of kids, sons of goats with positive result to lactoculture in at least one of mammary glands. Colostrum samples and blood were collected after delivery, 24 and 48 hours after delivery / birth. The diagnosis and monitoring of mastitis in animals were performed using the California Mastitis Test (CMT), somatic cell count and microbiological isolation. Total protein was measured by the biuret method, and the concentrations of immunoglobulin A (IgA), immunoglobulin G (IgG), transferrin, albumin and haptoglobin through eletrofoerese polyacrylamide gel containing sodium dodecyl sulfate (SDS-PAGE). The agents most isolated in microbiological culture were coagulase-negative Staphylococcus. There was no significant difference (p <0.05) between the acquisition of immunoglobulin G (IgG) in goats from goats with mastitis compared to infants originating free goat mammary infections. Similarly the gamma glutamyl transferase (GGT) was equal in the comparison between groups in all evaluated moments. The colostrum intake resulting from goats with mastitis caused no failure in the passive transfer of immunity in their fetuses.
Immunity of procurement in passive kids fed colostrum from goats with and without mastitis
Keywords: Immunoglobulins; Lactocultura; Passive transfer; Staphylococcus coagulase negative